2009
DOI: 10.1007/s11524-009-9405-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Power and Sexual Risk among Women in Community-Based Substance Abuse Treatment

Abstract: Relationship power has been highlighted as a major factor influencing women's safer sex practices. Little research, however, has specifically examined relationship power in drug-involved women, a population with increased risk for HIV transmission. Using baseline data from a National Institute on Drug Abuse Clinical Trials Network multisite trial of a women's HIV prevention intervention in communitybased drug treatment programs, this paper examined the association between sexual relationship power and unprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 57 publications
4
36
4
Order By: Relevance
“…Another study from South Africa observed a positive association between sexual power and consistent condom use, although these studies did not explicitly focus on the decision making dominance subscale of the SRPS, where our decision making variable was drawn 20. Campbell et al 32 argued that the decision making dominance subscale of the SRPS may be a more accurate predictor of condom use, as it captures women's relative power to her partner.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from South Africa observed a positive association between sexual power and consistent condom use, although these studies did not explicitly focus on the decision making dominance subscale of the SRPS, where our decision making variable was drawn 20. Campbell et al 32 argued that the decision making dominance subscale of the SRPS may be a more accurate predictor of condom use, as it captures women's relative power to her partner.…”
Section: Discussionmentioning
confidence: 99%
“…The RC subscale is explained by Campbell et al to encompass the ability to “act as one desires,” in the context of a relationship (Campbell et al, 2009). The direction of the associations we observed between RC subscale scores and the sexual risk variables is consistent with other studies of heterosexual couples.…”
Section: Discussionmentioning
confidence: 99%
“…HIV prevention research has highlighted gender inequality and the resulting power differential found in relationships between women and men as contributing factors in heterosexual HIV transmission and disproportionate rates of HIV among women (Campbell et al, 2009; Campbell, Tross, Hu, Pavlicova, & Nunes, 2012; Knudsen et al, 2008; Pulerwitz, Gortmaker, & DeJong, 2000). Power dynamics (also referred to as “relationship power dynamics” or “gendered power”) is a concept that encompasses a range of individual (empowerment), interpersonal (dominance and control in relationships) and social and structural factors (gender norms, economic inequalities).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, from a sociological perspective, it has been proposed that genderbased power imbalances play an important role in determining individuals' sexual behaviours (e.g., Amaro 1995). In several studies of non-homeless females from diverse ethnic backgrounds, individuals who were low in relationship power (e.g., decision-making abilities, assertiveness, control) demonstrated an increased risk of sexual risk behaviours and poor sexual health outcomes, including unprotected sex and hiv (e.g., Bralock and Koniak-Griffin 2007;Campbell et al 2009;Jewkes et al 2010). This power differential may make it difficult for girls and women to assert themselves sexually and to resist coercion in sexual situations (Tyler and Johnson 2006).…”
Section: Socio-demographic Risk Factorsmentioning
confidence: 99%